Sample geometry and efficiency determination of bremsstrahlung radiation of 90Sr on gamma detection systems - Turhan, Şeref; Zararsız, A.; Yücel, H. (Journal of Radioanalytical and Nuclear Chemistry, Vol. 269, No.1 (2006) 141–145, 2006)
The bremsstrahlung radiation energy spectra were produced by hard beta-emitters the 90Sr–90Y contaminated tea sample sources placed in a copper cylinder (cylinder counting geometry) and encapsulated in two Cu discs (sandwich counting geometry). These energy spectra were directly measured by using two separate gamma-ray spectrometers with a coaxial 110% efficient HpGe detector and a 110 cm3 HpGe well-type detector. The minimum detectable activity and the absolute efficiency of beta-activity for the sandwich and cylinder geometries were found to be 23 Bq. kg–1 and (1.67±0.04)% and 55 Bq. kg–1 and (2.61±0.05)%, respectively. These results indicate that the bremsstrahlung radiation counting method can be applied to some environmental studies when high efficient HpGe detectors, especially well-type HpGe are used.